2019
DOI: 10.1155/2019/2989048
|View full text |Cite|
|
Sign up to set email alerts
|

Outcomes of Programmed Cell Death Protein 1 (PD-1) and Programmed Death-Ligand 1(PD-L1) Inhibitor Therapy in HIV Patients with Advanced Cancer

Abstract: Due to HAART and consequent decline in mortality from infectious complications, HIV patients have an increasing burden of non-AIDS defining cancers. Data on their safety and efficacy is unknown as these patients were excluded from clinical trials due to concern of unforeseen side effects. Objectives. The main objective of our study was to evaluate the efficacy and safety profile of PD-1 and PD-L1 inhibitors in HIV patients being treated for advanced cancers and to assess the impact of these drugs on HIV status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…The latest study including 17 HIV-positive cancer patients showed that Checkpoint inhibitors seemed like to have comparable e cacy and tolerable adverse effects,and CD4 + Tlymphocyte cell count and viral load were not affected. In this study, the only one RCC patient with stage III responded to immunal thepapy with stable disease, and had slight side effects [22].…”
Section: Discussionmentioning
confidence: 59%
“…The latest study including 17 HIV-positive cancer patients showed that Checkpoint inhibitors seemed like to have comparable e cacy and tolerable adverse effects,and CD4 + Tlymphocyte cell count and viral load were not affected. In this study, the only one RCC patient with stage III responded to immunal thepapy with stable disease, and had slight side effects [22].…”
Section: Discussionmentioning
confidence: 59%
“…Moreover, PD-1 blockade has shown a synergistic effect with other latency reversing agents in several pre-clinical studies ( 8 , 13 ). However, similar to the low response rate observed for PD-1 blockade in patients with cancer, only one study confirmed that anti-PD-1 therapy appears to be useful in PLWH with cancer ( 45 ), necessitating efforts that are aimed at improving efficacy using combined regimens. This strategy was corroborated by a recent report which showed that reversal of HIV latency was achieved by blockade of multiple checkpoint receptors, PD-1, CTLA4, TIM3, and TIGIT without T cell stimulation, and this effect was significantly greater than that induced by latency reversal agents such as vorinostat and bryostatin ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…The latest study including 17 HIV-positive cancer patients showed that checkpoint inhibitors seemed like to have comparable efficacy and tolerable adverse effects, and CD4 + T lymphocyte cell count and viral load were not affected. In this study, only one RCC patient with stage III responded to immunal therapy with stable disease and had slight side effects [ 22 ].…”
Section: Discussionmentioning
confidence: 99%